Kontribusi Resiliensi Matematis terhadap Hasil Belajar Matematika - Fazriansyah, Muh Fajar; Sirri, Evi Latifatus; Faturohman, Ikhsan (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study aims to analyze the contribution of mathematical resilience to students' mathematics learning outcomes. Mathematical resilience is defined as the ability of students to persevere, recover, and adapt positively in facing difficulties or challenges in mathematics learning. This study employs a quantitative method using descriptive analysis, correlation analysis, and simple linear regression analysis techniques. The population of this study consists of Grade X students in the 2024/2025 academic year at MAN 3 Tasikmalaya. The sample comprises 30 students from class X-4, selected using a random sampling technique. The results show a significant positive correlation of mathematical resilience to mathematics learning outcomes. Mathematical resilience contributes 24.8% to mathematics learning outcomes, while the remaining 75.2% is determined by other factors. These findings indicate that students with higher levels of mathematical resilience tend to achieve better learning outcomes compared to less resilient students.